Recreational activities and psychological distress during the COVID-19 crisis: a cohort study from Norway - Rebecca Dyer Ånensen; Viggo Krüger; William Hazell; Gro Mjeldheim Sandal; Lars Thore Fadnes (BMC Public Health)
Abstract Background This study aims to assess the relationship between engaging in recreational activities before the pandemic and levels of psychological distress during the pandemic. Methods Data from a cohort study (n = 16,212) collected at three time points (April 2020, January 2021, and May 2022) in Bergen, Norway, were analysed via a linear mixed model. Associations between psychological distress and five dimensions of recreational activities were assessed, both at baseline and over time. Results Regular physical activity before the pandemic was linked to lower psychological distress at baseline, whereas for cultural audience participation, this relationship was inverted. Over time, regular cultural audience participation before the pandemic was associated with a slight reduction in psychological distress. No clear baseline associations or significant changes over time were found for cultural practitioner, social networking, or volunteering/religious activities. Conclusions These findings suggest that there are links between recreational activities and psychological distress during a crisis, with cultural audience participation possibly reducing distress over time.